Some Characterizations of Strongly Semisimple Ordered Semigroups (Communications in Mathematical Research, 2021)
In this paper, the concept of quasi-prime fuzzy left ideals of an orderedsemigroup $S$ is introduced. Some characterizations of strongly semisimple orderedsemigroups are given by quasi-prime fuzzy left ideals of $S$. In particular, we provethat $S$ is strongly semisimple if and only if each fuzzy left ideal of $S$ is the intersectionof all quasi-prime fuzzy left ideals of $S$ containing it.
Keywords: ordered semigroup; ordered fuzzy point; quasi-prime fuzzy left ideal; strongly semisimple ordered semigroup.